Analisis pendekatan tpack pada materi KPK siswa kelas IV - Nadila Lutfiah Amartya (Nautical : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
The development of technology and information is growing very rapidly in the 21st century. Education is required to be selective in the development of an increasingly modern era. TPACK is knowledge and skills in applying technology to learning. This study uses a descriptive qualitative approach. The subjects of this study were fourth grade students consisting of a class of 25 students who were taken randomly. The results obtained in this study are that all students use the media google teams, whatsap in learning, google form is used in carrying out the task of evaluating the KPK material. Technological Knowledge (TK) Pedagogical Knowledge (PK), Content Knowledge (CK), Pedagogical Content Knowledge (PCK), Tecnological Content Knowledge (TCK) Tecnological Pedagogical Knowledge (TPK) Tecnological Pedagogical Content Knowledge (TPACK) has been applied to students at SDN City Surabaya. Students use learning videos with the Google Teams web link. Once a week there are practice questions through the Google Form used in the evaluation of learning. The obstacles experienced by students are that they are often controlled by inadequate signals such as complaints of internet quotas that run out quickly, cellphone or laptop memory that fills up quickly. The solution to overcome this is to do face-to face online every morning according to the agreed schedule, delete files that are no longer used, download learning videos given by the teacher with a duration that is not too long.